Aspectos etnográficos na obra documental de António Campos - Francisco Serafim, José (2022)
The objective of this text is to debate the documentary work of António Campos from the point of view of its relationship with ethnography. After analyzing the director's documentaries I highlight aspects that bring the films closer to ethnographic cinema. The exemplary film for this proposal is the documentary A almadraba atuneira made in 1961, which presents the different stages of tuna fishing in the south of Portugal.